Pendekatan Syarah Ibn al-‘Attar dalam Al-Uddah fi Sharh Umdah fi al-Ahadith al-Ahkam: Analisis Sosio-Historis - Chovifah, Anisatul; Muhid, Muhid; Nurita, Andris; Verawati, Sellyana; Hasbulloh, Moh (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
This study examines the sharh methodology employed by Ibn al-‘Attar in his work Al-Uddah fi Sharh Umdah fi al-Ahadith al-Ahkam. Using a qualitative method and a library research approach, this research focuses on the socio-historical analysis of Ibn al-‘Attar's intellectual background and the influence of the Shafi’i school on his works. The findings indicate that Ibn al-‘Attar applied the tahlili (analytical) method in his sharh, aimed at facilitating readers, particularly beginners, in understanding legal hadiths. Social factors, especially the Shafi’i culture in Damascus, along with the significant influence of his teacher, Imam Nawawi, greatly shaped Ibn al-‘Attar's approach. The book demonstrates a clear system, providing detailed explanations based on the companions' narrations and their associated rulings. This study contributes significantly to understanding the role of sharh in the development of hadith studies and the influence of the Shafi’i school on hadith interpretation within Islamic scholarly traditions.Abstrak: Kajian ini membahas metodologi syarah yang digunakan oleh Ibn al-‘Attar dalam karyanya Al-Uddah fi Sharh Umdah fi al-Ahadith al-Ahkam. Dengan menggunakan metode kualitatif dan pendekatan kepustakaan, penelitian ini berfokus pada analisis sosio-historis yang melatarbelakangi pemikiran Ibn al-‘Attar serta pengaruh mazhab Syafi’i terhadap karya-karyanya. Temuan menunjukkan bahwa Ibn al-‘Attar menerapkan metode tahlili (analisis) dalam syarahnya, yang ditujukan untuk memudahkan pembaca, terutama pelajar pemula, dalam memahami hadis-hadis hukum. Faktor sosial, terutama budaya Syafi’i di Damaskus, serta pengaruh besar dari gurunya, Imam Nawawi, sangat memengaruhi pendekatan Ibn al-‘Attar. Kitab ini juga menunjukkan sistematika yang jelas, dengan penjelasan yang rinci dan berbasis pada riwayat sahabat serta hukum-hukumnya. Penelitian ini memberikan kontribusi penting dalam memahami peran syarah dalam perkembangan ilmu hadis dan pengaruh mazhab Syafi’i terhadap interpretasi hadis dalam tradisi keilmuan Islam.